Dynamics of bacterial community exposed to hydrocarbons and oleophilic fertilizer in high-Arctic intertidal beach - RØberg, stian; Østerhus, Jan ivar; Landfald, Bjarne (Polar Biology, 2011)
Exposure of pristine microbial environments to hydrocarbon contamination stimulates growth of the initially small fraction of indigenous hydrocarbon-degrading bacteria. Custom-made oleophilic fertilizers have been demonstrated to promote oil bioremediation by boosting this proliferation. In the present study, the temporal dynamics of the bacterial community structure and the individual influences of hydrocarbons and an oleophilic fertilizer in shaping the community structure was explored during a 78 days bioremediation experiment in a high-Arctic intertidal beach environment. A combination of cultivation independent 16S rRNA gene length-heterogeneity polymerase chain reaction (LH-PCR) profiling and identification of hydrocarbon-degrading isolates based on partial 16S rRNA gene sequences was employed. LH-PCR community profiles in the fertilizer alone and fertilized kerosene plots were largely indistinguishable throughout the experimental period, while kerosene alone plots showed a markedly different composition of dominant groups. This pointed to the fertilizer as the more decisive factor in shaping the community structure. Most prominent LH-PCR fragments which emerged after kerosene or fertilizer addition could be provisionally assigned to bacterial taxa through coinciding LH-PCR fragment lengths with hydrocarbon degrading isolates obtained from the same type of experimental units. However, a few quantitatively significant LH-PCR groups had no counterparts among the cultivated bacteria. One of these was affiliated to a hitherto unspeciated subgroup within the Alkanindiges/Acinetobacter clade of Moraxellaceae by a 16S rRNA gene cloning approach.